The Mediating Role of Academic Buoyancy and Academic Achievement Motivation in the Relationship between Basic Psychological Needs and Psychological Well-being at Al-Qadisiyah University, Iraq - Sabti Tamimi, Makarem; Khayatan, Felor; Fadhil Abd Ali, Thaeir; Mahdad, Ali (KMAN Counseling & Psychology Nexus, 2025)
Psychological well-being is one of the most influential factors affecting students’ efforts and performance. Hence, this study aimed to determine the mediating role of academic buoyancy and academic achievement motivation in the relationship between basic psychological needs and psychological well-being among students at Al-Qadisiyah University in Iraq. This research follows a correlational method. The statistical population comprised students at Al-Qadisiyah University in Iraq during the spring of 2024. From this population, 239 students were selected through convenience sampling and responded to Psychological Well-being (Ryff & Keyes, 1995), Academic Buoyancy (Hossein Chari & Dehghani Zadeh, 2012), Academic Achievement Motivation (McInerney & Sinclair, 1991) Basic Psychological Needs (Gagné, 2003) questionnaires. The data were analyzed using Pearson correlation coefficients and structural equation modeling (SEM) through SPSS version 26 and AMOS version 26. The results showed a significant relationship between basic psychological needs and psychological well-being, academic buoyancy, and academic achievement motivation (p < 0.05). The results of Structural equation modeling revealed that academic buoyancy and academic achievement motivation act as complete mediators in the relationship between basic psychological needs and psychological well-being. Based on the findings of this study, the role of basic psychological needs, academic buoyancy, and academic achievement motivation should be emphasized in academic setting to foster greater student psychological well-being.